Search for η'-mesic nuclei using (p, d) reaction with FRS/Super-FRS at GSI/FAIR. (December 2020) - Tanaka, Y. K.; Bagchi, S.; Benlliure, J.; Dickel, T.; Drozd, V.; Ekawa, H.; Fujioka, H.; Geissel, H.; Goldenbaum, F.; Guo, C.; Haettner, E.; Harakeh, M. N.; et al.
Abstract: We plan a semi-exclusive measurement of the 12 C( p, dp ) reaction to search for η'-mesic nuclei, aiming at investigating in-medium properties of the η′-meson. We employ a 2.5 GeV proton beam impinging on a carbon target to produce η′-mesic 11 C nuclei via the 12 C( p, d )η′⊗ 11 C reaction. Using coincidence measurements of the forward going deuterons, important for missing-mass spectroscopy, and decay protons emitted from the η′-mesic nuclei. for event selection will provide a high experimental sensitivity to observe η'-mesic nuclei. We will perform the measurements by combining the WASA detector system with the fragment separator FRS at GSI and also with the Super-FRS at FAIR in the future. The plan of the experiments and the present status are reported.